Age-period-cohort analysis of autism spectrum disorders-related prevalence and DALYs: based on the Global Burden Of Disease Study 2021 - Li, Dong; Liang, Zhide; Miao, Chuyuan; Li, Lan; Li, Chenmu (Frontiers in Psychiatry, 2025)
BackgroundThe Sustainable Development Goals (SDGs) call for systematic monitoring to optimize child development outcomes. As a developmental disorder affecting children and adults, Autism Spectrum Disorder (ASD) not only impacts individual social functioning but also places a burden on families and society. A detailed analysis of the latest global burden data on ASD can assist stakeholders in formulating support policies and interventions, thereby helping to meet the health needs of ASD.MethodsWe used data from the Global Burden of Disease Study 2021 (GBD 2021), compiled by the Institute for Health Metrics and Evaluation (IHME). Data were obtained through the Global Health Data Exchange (GHDx) and covered 204 countries and territories from 1990 to 2019. Variables included ASD-related prevalence, mortality, disability-adjusted life years (DALYs), age-standardized rates, and the sociodemographic index (SDI).ResultsExposure to autism spectrum disorders contributed to 61823540 prevalence and 11544038 DALYs globally in 2021. Males and younger adults were high-risk populations. Higher socio-demographic index (SDI) regions were high-risk areas. The disease burden varied considerably across the GBD regions and the countries. From 1990 to 2021, the number of cases increased. The predicted results showed that the disease burden for both genders would still increase from 2022 to 2046. Countries or regions with a higher SDI have greater burden improvement potential.ConclusionThe global burden of ASD has shown a continuous upward trend, with some differences observed across gender, age groups, and SDI regions. In terms of gender, the burden of ASD among females may be underestimated. Regarding age groups, the aging process has highlighted the urgent need to address ASD in the elderly population. High-SDI regions should place greater emphasis on improving diagnostic methods and implementing precise interventions, while middle- and low-SDI regions should focus on raising public awareness and enhancing screening capabilities.